The Semiotics of the Body in Ali Badr’s Novel Al Kafira - Sarkawt Koreal Ibrahim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This paper provides a detailed analysis of an important topic which is the narrative representations of the female body, i.e. the semiotics of the body, through an extensive study of Ali Badr’s novel Al Kafira (The Infidel Woman). Badr is an Iraqi poet and novelist, who published fifteen novels, one collection of stories, six philosophical writings, three plays, and two poetry collections, and published many studies in Arab and international newspapers, such as Al-Hayat, Al-Akhbar, Al-Safir, Le Mond, Liberation, The Washington Post, The Sunday Times, and The Independent. The research falls into two sections, preceded by an introduction to the body in general and followed by a conclusion with the most important findings of the research. The first section is entitled the identity of the body and its authority, which is divided into two parts: the first is devoted to the violated body, and the second discusses the liberated body. The second section focuses on the signs of the body and its manifestations, which revolve around (sex, love, fear, and violence). The body is a double-edged icon, it is, on the one hand, the point of strength of women to differentiate their body from that of men, and on the other hand a weak point due to the religious and cultural assumptions on her body. These assumptions justify the stereotypical, belittling perception of the female body as frail and lacking of special entity, unlike the male body, which has a special entity surrounded by an aura of sacredness. Furthermore, the woman has been portrayed as a minor being whose body she does not own but was commodified and bestowed the customs to the man. So, the narrative clearly drives attention to the woman's body in its erotic aspect (lust and sex), after which the object of inspiration for men, as if this aspect is the origin of the woman. As for the mind, it is accidental and secondary, which leads to neglecting the aspect of women's social being and focusing solely on their biological aspect.